Analyzing the Code of Hammurabi: Exploring Ancient Legal Principles and Their Relevance in Modern Law - Saputra, Beny; Putra, David Aprizon; Bene, OlivÃ©r (NEGREI: Academic Journal of Law and Governance, 2024)
This study examines the Code of Hammurabi, an ancient legal code that dates to early human history, to investigate its old legal ideas and evaluate their ongoing significance in contemporary legal systems. This study seeks to clarify the fundamental concepts that underlie Hammurabi's rules and their lasting influence on modern legal thinking by conducting a thorough investigation of the Code's provisions and historical background. This research aims to provide significant insights into the development of legal norms and their application in addressing current legal difficulties by analyzing important elements such as justice, equity, and societal order as outlined in the Code. This study examines the degree to which Hammurabi's legal ideas align with contemporary legal frameworks. It provides insightful analysis on the lasting significance and flexibility of ancient legal precedents in creating modern legal jurisprudence. This research enhances our comprehension of the historical origins of law and its enduring importance in contemporary legal discussions.